2020
DOI: 10.1111/tbed.13743
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors associated with occurrence of COVID‐19 among household persons exposed to patients with confirmed COVID‐19 in Qingdao Municipal, China

Abstract: Summary Tracing and isolation of close contacts is used to control outbreaks of coronavirus disease 2019 (COVID‐19) in China. However, risk factors associated with occurrence of COVID‐19 among close contacts have not been well described. 106 household contacts were included in this study, of whom 19 were developed into COVID‐19 cases and the secondary attack rate was 17.9%. Multivariable analysis showed increasing risk of occurrence of COVID‐19 among household contacts associated with female of inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(45 citation statements)
references
References 21 publications
2
42
1
Order By: Relevance
“…Secondary attack rates were not significantly different when restricting to 38 studies 19 , 20 , 22 , 23 , 26 , 27 , 28 , 29 , 30 , 31 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 42 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 54 , 55 , 56 , 57 , 60 , 62 , 63 , 65 , 67 , 68 , 69 , 72 with low or moderate risk of bias (15.6%; 95%, 12.8%-18.5%) (eFigure 4 in the Supplement ). There were no significant differences in secondary attack rates between 21 studies in China 22 , 27 , 31 , 36 , 37 , 39 , 45 , 46 , 48 , 58 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 70 , …”
Section: Resultsmentioning
confidence: 90%
See 3 more Smart Citations
“…Secondary attack rates were not significantly different when restricting to 38 studies 19 , 20 , 22 , 23 , 26 , 27 , 28 , 29 , 30 , 31 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 42 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 54 , 55 , 56 , 57 , 60 , 62 , 63 , 65 , 67 , 68 , 69 , 72 with low or moderate risk of bias (15.6%; 95%, 12.8%-18.5%) (eFigure 4 in the Supplement ). There were no significant differences in secondary attack rates between 21 studies in China 22 , 27 , 31 , 36 , 37 , 39 , 45 , 46 , 48 , 58 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 70 , …”
Section: Resultsmentioning
confidence: 90%
“…We identified 54 relevant published studies that reported household secondary transmission, with 77 758 participants (eTable 1 in the Supplement ). 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 A total of 16 of 54 studies (29.6%) were at high risk of bias, 27 (50.0%) were moderate, and 11 (20.4%) were low (eTable 2 in the Supplement ). Lower quality was attributed to studies with 1 or fewer test per contact (35 studies [64.8%]), small sample sizes (31 [57.4%]), a...…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We identified only two other studies that considered the impact of testing delays on household transmission; Xin et al 17 and Wang et al 14 examined the time from illness onset to laboratory confirmation. They reported hazard ratios for household transmission of 2·32 (95% CI 0·89 - 6·10) (<7-day delays versus ≥7-day delays) calculated from 106 households, and 2·35 (95% CI 0·63 - 8·77) (<3-day delays versus ≥3-day delays) calculated from 124 households, respectively.…”
Section: Discussionmentioning
confidence: 99%